Proceedings of the Ninth International Conference on Dependability and Complex Systems DepCoS-RELCOMEX. June 30 - July 4, 2014, Brunów, Poland - Zamojski, Wojciech; Mazurkiewicz, Jacek; Sugier, Jarosław; Walkowiak, Tomasz; Kacprzyk, Janusz (Advances in Intelligent Systems and Computing,, 2014)
DepCoS - RELCOMEX is an annual series of conferences organized by Wrocław University of Technology to promote a comprehensive approach to evaluation of system performability which is now commonly called dependability. In contrast to classic analyses which were concentrated on reliability of technical resources and structures built from them, dependability is based on multi-disciplinary approach to theory, technology, and maintenance of a system considered to be a multifaceted amalgamation of technical, information, organization, software and human (users, administrators, supervisors, etc.) resources. Diversity of processes being realized (data processing, system management, system monitoring, etc.), their concurrency and their reliance on in-system intelligence often severely impedes construction of strict mathematical models and calls for application of intelligent and soft computing methods. This book presents the proceedings of the Ninth International Conference on Dependability and Complex Systems DepCoS-RELCOMEX, which took place in Brunów Palace, Poland, from 30th June to 4th July, 2014. The articles selected for this volume illustrate the variety of topics that must be included in system dependability analysis: tools, methodologies and standards for modelling, design and simulation of the systems, security and confidentiality in information processing, specific issues of heterogeneous, today often wireless, computer networks, or management of transportation networks.  .